Assessing clinical reasoning in physical therapy: discriminative validity of the Reasoning 4 Change instrument. (December 2022) - Elvén, Maria; Boersma, Katja; Overmeer, Thomas
Abstract: Objectives: To evaluate discriminative validity of the Reasoning 4 Change (R4C) instrument by investigating differences in clinical reasoning skills between first semester, final semester physical therapy students and physical therapy experts. Design: Cross-sectional design Setting: University and physical therapy practice Participants: Students from the first ( n = 87) and final semester ( n = 47) of an entry-level physical therapy program and experts in physical therapy with a behavioral medicine approach ( n = 14). Methods: The students and experts answered the web-based R4C instrument on one occasion. The R4C instrument includes four domains designed to assess physical therapists' clinical reasoning skills with a focus on supporting clients' behavior change and has demonstrated acceptable content validity, convergent validity and reliability. Data was analyzed with one-way analysis of variance and Games-Howell post hoc test. Results: Differences in all domains and subscale scores were found between the three groups. Pairwise comparisons demonstrated that experts scored higher (better clinical reasoning skills) than first semester students in all domains and subscales; and higher scores than final semester students, except for two subscales. Final semester students scored higher than first semester students, except for one subscale. Conclusions: The findings highlight differences in clinical reasoning skills focusing on clients' behavior change among physical therapy students with different degrees of training and education in clinical reasoning and physical therapists with extensive experience and expertise. The results provide evidence for the discriminative validity of the R4C instrument which support the use of the R4C instrument in education, research and clinical practice. Contribution of the Paper: The study results provide evidence for the discriminative validity of the R4C instrument, thus strengthening its validity evidence. The findings highlight the differences in clinical reasoning skills focusing on clients' behavior change amongst first semester students, final semester students and physical therapy experts. The R4C instrument may be used as part of regular quality assurance of physical therapy curricula and investigations of students' and practitioners' client-centered approach and behavioral considerations in clinical reasoning. For example, repeated measures over time may reveal changes in students' learning and comparisons between groups may identify strengths and weaknesses in students' and practitioners' clinical reasoning, which may guide curricula modifications and interventions in practice.